Comparison of Epidural Butorphanol with Neostigmine and Epidural Sufentanyl with Neostigmine for First Stage of Labor Analgesia: A Randomized Controlled Trial - Chaurasia, Manoj (Anesth Essays Res, 2017)
BACKGROUND: Epidural administration of neostigmine appears to be safe in the obstetric population. Recently, few studies have concluded 10 μg sufentanil to be an effective adjuvant with epidural neostigmine in providing labor analgesia. However, no study has evaluated the analgesic effect of epidural butorphanol with neostigmine for the same. MATERIALS AND METHODS: The parturients were randomly allocated to one of the three study groups - Group A (n = 30) received butorphanol 1 mg and neostigmine 7 μg/kg. Group B (n = 30) received sufentanil 10 μg and neostigmine 7 μg/kg. Group C (n = 30) received neostigmine 7 μg/kg and 0.9% normal saline. Maternal hemodynamic parameters and fetal heart rate (FHR) were continuously monitored. The level of sensory and motor block, and visual analog scale (VAS) pain score were recorded at designated time points. In addition, the total duration of analgesia, duration of labor, mode of delivery, and any maternal or fetal adverse effects were also recorded. STATISTICAL ANALYSIS USED: A one-way analysis of variance (ANOVA) with post hoc Tukey's test was used to compare mean value among the three groups for age, height, weight, gestational age, and cervical dilatation. Repeated measure ANOVA was used to compare mean difference among the time points and also the trend among the various time points for hemodynamic parameters, VAS pain score, and FHR. For inter-group comparison among the groups, post hoc Tukey test was used. RESULTS: There was a statistically significant longer effect of analgesic drug in Group B with respect to Group A and C (P < 0.001); however, the parturient in Group C had minimum duration of analgesia. Epidural neostigmine combined with sufentanil produces effective analgesia in early labor (VAS <30 within 10 min in 63.3% of parturient and within 15 min in 83.3% parturient) with average duration of 111.67 ± 24.51 min without motor block or other side effect in mother and fetus. No significant effect was observed in the duration of labor and mode of delivery in-between the two groups, and none of the patients in any group had any maternal or fetal side effects. CONCLUSION: Epidural combination of sufentanil with neostigmine provided better pain relief in terms of the total duration of analgesia and the reduction in VAS pain scores at various time points in the initial 30 min of epidural administration of drugs during the first stage of labor in parturient when compared to the epidural combination of butorphanol with neostigmine.